Studi Perbandingan Beban Gempa Pada Gedung Rawat Inap Non Bedah RSUD Dr. H. Abdul Moeloek, Bandar Lampung Dengan Analisis Respon Spektrum Sesuai SNI 1726:2012 dan SNI 1726:2019 - Hania Cipta, Ade Permata; Isneini, Mohd.; Husni, Hasti Riakara; Kusnadi, Andi (Universitas Lampung, 2023)
The rapidly growing population is directly proportional to the increasing amount of land use, especially in urban areas, one of which is in the city of Bandar Lampung. The construction of vertical structures or high-rise building structures is an option in overcoming the limited land. However, high-rise building structures are considered to be risky to lateral loads such as earthquake loads, so that in planning, earthquake loads must be considered.This study aims to determine differences in response to the earthquake acceleration spectrum in the City of Bandar Lampung, especially the Non-Surgical Inpatient Building at Dr. H. Abdul Moeloek based on SNI 1726:2012 and SNI 1726:2019. Based on the results of this study, it was found that due to the influence of the earthquake the input spectrum response was in accordance with SNI 1726:2012 and SNI 1726:2019, the base shear force due to the earthquake spectrum response for SNI 1726:2012 was 12900.4864 kN and SNI 1726:2019 was 14931.0787 kN . Interstory drift between levels that occur in the structure are still in the safe category because they do not exceed the story drift allowable levels, 48.4615 mm.